Springback prediction of mild steel sheet on V-bending - Mohd Hizir Arafar, Tambun (2010)
Bending is common process in manufacturing industry. This process is used insheetmetal deformation. Although bending is small part of sheet metal forming, but the research in bending has great intention to industry in term of material selection, production cost, productivity and quality control. So term in engineering, bending means forming of a metal part, by pressure, into a curved or angular shape, or the stretching or flanging of it along a curved path. The forming of a metal to a desired shape by pressure depends on material properties. Therefore, industry does need this bending analysis. Bending analysis also will take the spring back analysis as one of the part. Through this project, bending analysis can be made in term of knowing about spring back, and the related cause in bending process such as types of materials, types of bending, and the thickness of the material. These will give effect to the bending process in order to make an analysis to suite the material selection in industry’s production lines. In addition, the companies need to reduce their cost in manufactured product but want to produce high quality product. Therefore, this analysis is important as a guide to mastering the bending analysis by analytical and numerical. This will take practicing of software which is Finite Element Analysis (FEA) software will be one of the element in this project. Methodology that used in this project, start with selection of material and type of bending. Then it goes by make the bending process at bending machine. The same specification of the bended sample will be analyzed in Abaqus version 6.7 software by simulate it. Finally, the overall analysis is done and it’s achieved the objective successfully. The result of the research will be elaborate in the result and discussion chapter.